Bortezomib Treatment Produces Nocifensive Behavior and Changes in the Expression of TRPV1, CGRP, and Substance P in the Rat DRG, Spinal Cord, and Sciatic Nerve. (27th April 2014) - Quartu, M.; Carozzi, V. A.; Dorsey, S. G.; Serra, M. P.; Poddighe, L.; Picci, C.; Boi, M.; Melis, T.; Del Fiacco, M.; Meregalli, C.; Chiorazzi, A.; Renn, C. L.; et al.
Abstract : To investigate neurochemical changes associated with bortezomib-induced painful peripheral neuropathy (PN), we examined the effects of a single-dose intravenous administration of bortezomib and a well-established "chronic" schedule in a rat model of bortezomib-induced PN. The TRPV1 channel and sensory neuropeptides CGRP and substance P (SP) were studied in L4-L5 dorsal root ganglia (DRGs), spinal cord, and sciatic nerve. Behavioral measures, performed at the end of the chronic bortezomib treatment, confirmed a reduction of mechanical nociceptive threshold, whereas no difference occurred in thermal withdrawal latency. Western blot analysis showed a relative increase of TRPV1 in DRG and spinal cord after both acute and chronic bortezomib administration. Reverse transcriptase-polymerase chain reaction revealed a decrease of TRPV1 and CGRP mRNA relative levels after chronic treatment. Immunohistochemistry showed that in the DRGs, TRPV1-, CGRP-, and SP-immunoreactive neurons were mostly small- and medium-sized and the proportion of TRPV1- and CGRP-labeled neurons increased after treatment. A bortezomib-induced increase in density of TRPV1- and CGRP-immunoreactive innervation in the dorsal horn was also observed. Our findings show that bortezomib-treatment selectively affects subsets of DRG neurons likely involved in the processing of nociceptive stimuli and that neurochemical changes may contribute to development and persistence of pain in bortezomib-induced PN.